Time-resolved in situ nanoparticle size evolution during magnetron sputtering onto liquids - Eneren, Pinar; Sergievskaya, Anastasiya; Aksoy, Yunus Tansu; Umek, Polona; Konstantinidis, Stephanos; Vetrano, Maria Rosaria (Nanoscale advances, 2023)
Despite extensive research since 1996, there are still open questions regarding the primary location of the nucleation process, the growth mechanism of the nanoparticles (NPs), and the influence of the liquid properties on the ultimate size of the NPs for the magnetron sputtering of metals onto liquids. Hence, for the first time to the authors' knowledge, the particle size evolution is in situ and in real-time examined during and after the sputtering of the silver atoms onto silicone oil, i.e. , Sputtering onto Liquids (SoL) process. The particle size distribution (PSD) is measured via the Light Extinction Spectroscopy (LES) technique, and the deposition rate and stirring speed effects on the PSDs are analyzed. Based on De Brouckere mean diameters, the size evolution of silver nanoparticles (Ag NPs) over time is monitored. Ag NPs bigger than 20 nm are detected, and the PSDs are shown to be poly-disperse, which is also supported by the ex situ TEM measurements and in situ time-resolved absorption spectra. Moreover, it is shown that aggregation and growth of Ag NPs occur both at the plasma–liquid interface and inside the silicone oil during and after the magnetron sputtering. Despite the same amount of deposited silver, the growth kinetics of Ag NPs in silicone oil vary at different deposition rates. In particular, at higher deposition rates, larger NPs are formed. Stirring is seen to help disaggregate the particle lumps. Faster stirring does not substantially influence the final size but promotes the formation of smaller NPs (<20 nm). Also, low colloidal stability of Ag NPs in silicone oil is observed.